2004
DOI: 10.1248/cpb.52.961
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Water Solubility of Fullerene by Cogrinding with Mixture of Cycloamyloses, Novel Cyclic .ALPHA.-1,4-Glucans, via Solid-Solid Mechanochemical Reaction

Abstract: Improvement of solubility for fullerene (C 60 ) was studied by cogrinding with cycloamyloses using a ball mill in the solid state. Cycloamylose is a novel cyclic a a-1,4-glucan produced from synthetic amylose by enzymatic reaction. Although sample solutions showed a pale yellow for the initial period of cogrinding with cycloamyloses and C 60 , the color varied to brown after 48 h. Subsequently, the solubility of C 60 was improved markedly to 560 (m mg/ml) at 96 h. From powder X-ray diffraction analysis, the pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 22 publications
0
21
0
Order By: Relevance
“…In particular, the LR-CD mixture showed a high solubilization effect for cholesterol in comparison with α-, β-and γ-CD. Furthermore, the Tomono group also reported the improvement of the solubility of fullerene (C 60 ) by co-grinding with LR-CD mixture in the solid state (64). The molecular state of C 60 in the complex was evaluated using powder X-ray diffraction, UV-VIS spectroscopy and dynamic light scattering measurement.…”
Section: Application Of Lr-cdsmentioning
confidence: 99%
“…In particular, the LR-CD mixture showed a high solubilization effect for cholesterol in comparison with α-, β-and γ-CD. Furthermore, the Tomono group also reported the improvement of the solubility of fullerene (C 60 ) by co-grinding with LR-CD mixture in the solid state (64). The molecular state of C 60 in the complex was evaluated using powder X-ray diffraction, UV-VIS spectroscopy and dynamic light scattering measurement.…”
Section: Application Of Lr-cdsmentioning
confidence: 99%
“…11 Deep cavity calixarenes which have a larger hydrophobic surface area are effective in water solubilising large hydrophobic molecules, for example b-carotene in the presence of p-4-sulfonatophenyl or benzyl calix[n]arenes. 12 Herein we show that under certain conditions p-sulfonatocalix [4]arene is effective in solubilising fullerenes C 60 and C 70 in water. This is despite the well known lack of complementarity of size and shape of the cavity of this calixarene relative to the fullerenes.…”
Section: Introductionmentioning
confidence: 84%
“…Fukami et al have developed a C 60 solubilisation method involving mechanochemically co-grinding the fullerene with cycloamyloses, in doing so avoiding the use of organic solvents. 4 Deguchi et al found that C 60 particles as small as 20 nm are readily produced by grinding the fullerene in an agate mortar, the nanoparticles being successfully dispersed in water with or without the aid of a surfactant such as sodium dodecylsulfate. 5 Dispersed nanoparticles of fullerenes in water devoid of a stabilizer have also been developed by Scrivens et al This involves dissolving C 60 in an increasing content of polar molecules, starting with benzene, THF, acetone and then finally water.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The interesting role of CDs in drug delivery systems is not limited to their role in nanoparticle formation and characteristics-they can also be used in supramolecular structures; for example, two CDs most often b-CD, or their derivatives can form complexes with fullerenes C 60 [117][118][119][120][121], making them water-soluble products and thus easier to use for biological applications, among which are anti-HIV or DNA cleavage activities [122][123][124].…”
Section: Discussionmentioning
confidence: 99%